Preparation of highly hydrophobic cellulose based surfaces by silica particles and fluorosiloxane deposition - Wierzba, Patrycja; Krasiński, Andrzej (Видавництво Львівської політехніки, 2017)
This work is focused on modification of cellulose filters surface in order to hydrophobise a material and decrease water drop adhesion to its surface. Proposed modification methods include deposition of silica particles to obtain desired material roughness and coating material with 1H,1H,2H,2H-perfluorooctyl triethoxysilane (FOTS) to decrease its surface energy.
Keywords: cellulose filter media; silica particles; 1H 1H 2H 2H-perfluorooctyl triethoxysilane (FOTS); roughness; hydrophobicity